Design of surface nanostructures for chirality sensing based on quartz crystal microbalance - Ma, Yinglin; Xiao, Xiangyun; Ji, Qingmin (Beilstein Journal of Nanotechnology, 2022)
Quartz crystal microbalance (QCM) has been widely used for various sensing applications, including chirality detection due to the high sensitivity to nanogram or picogram mass changes, fast response, real-time detection, easy operation, suitability in different media, and low experimental cost. The sensing performance of QCM is dependent on the surface design of the recognition layers. Various strategies have been employed for studying the relationship between the structural features and the specific detection of chiral isomers. This review provides an overview of the construction of chiral sensing layers by various nanostructures and materials in the QCM system, which include organic molecules, supermolecular assemblies, inorganic nanostructures, and metal surfaces. The sensing mechanisms based on these surface nanostructures and the related potentials for chiral detection by the QCM system are also summarized.
Keywords: assembled nanostructure; chiral surface; chirality recognition; quartz crystal microbalance (QCM); sensing applications; surface architecture